Simplify 4x + 3 = 2x + 8 2x = 5 x =2½
5x+2x-3y+y = (5+2)x+(-3+1)y = 7x - 2y
I assume you wish to simplify the expression (x - 2)/(3x + 9) . (2x + 6)/(2x - 4) = (x - 2)(2x + 6) / [(3x + 9)(2x - 4)] = 2(x - 2)(x + 3) / [6(x + 3)(x - 2)] = 1/3.
Without parentheses, 3 x 4 = 12 2x + 12 factors to 2(x + 6)
you need to reorder the problem by manipulating the numbers -2x-7=-x+13 group your variables and constants thus -x-2x=7+13 simplify -3x=20 simplify again x=-20/3
2x + 4x + 3 = 6x + 3
x - 2x + 3 = 3 - x
Simplify 4x + 3 = 2x + 8 2x = 5 x =2½
3(x+y)
-7 + 2(x-3) = -7+2x-6 = 2x - 13
5x+2x-3y+y = (5+2)x+(-3+1)y = 7x - 2y
I assume you wish to simplify the expression (x - 2)/(3x + 9) . (2x + 6)/(2x - 4) = (x - 2)(2x + 6) / [(3x + 9)(2x - 4)] = 2(x - 2)(x + 3) / [6(x + 3)(x - 2)] = 1/3.
Without parentheses, 3 x 4 = 12 2x + 12 factors to 2(x + 6)
If there are no equals you can simplify this by collecting all the x values together and use the addition property of signed numbers. 2x+4x-5x+x=2x; 4+3=7. 2x+7 is the simplified statement.
OK, SO 15x-3 = 2x+1 15x - 3 + 3 = 2x + 1 + 3 (add three to each side) 15x=2x+4 (simplIfy) 15x-2x=2x-2x+4 (subtract 2x from each side) 13x=4 (simplify) (13x/13)=(4/13) (divide each side by 13) x≈0.30769231
2
(4x3)+(20x2)+(2x-3) if you simplify it down first: (12)+(40)+(2x-3) because we aren't multiplying, and there is no negative signs between brackets, we can just take out the brackets and simplify: 12 + 40 + 2x - 3 = 60 + 2x - 3 =57 + 2x =2x + 57 to factorise this, 2(x+28)+1 this is it factorised, but you can have lots of answers. the simplest form is 2x + 57. double check your signs are right, and you've written down the question properly. * * * * * 12 + 40 = 60? Since when? In any case, i suspect the questioner intended 4xcubed plus 20xsquared plus 2x minus 3 but the browser does not like superscripts.